Tillandsia landbeckii secures high phenotypic variation despite clonal propagation at the dry limits of plant life in the Atacama Desert - Jabbusch, Sarina; Koch, Marcus (Perspectives in plant ecology, evolution and systematics, 2025)
Hyperarid desert systems are among the most extreme and life-limiting biotas on Earth and lack almost any rainfall such as the Atacama Desert in northern Chile. In this study, we explored Tillandsia landbeckii loma vegetation consisting of only one single plant species that often covers square kilometers and is dependent on regular fog events as the most important water supply. We assessed growth and fitness parameters in the field and in cultivation; individual plants from nine permanent field study plots were collected and studied for phenotypic variation and plasticity under greenhouse conditions focusing on temperature and humidity. Individuals studied in the field and in cultivation have been genotyped using ddRAD analyses. The growth-related phenotypic variation shows very fine-scale adaptations to environmental gradients reflecting fog availability, and phenotypic variation is shown to be large. Genetic data indicate that Tillandsia landbeckii propagates mostly clonally, and various clones exhibit increased phenotypic variation and also prevail in the population. Our results suggest that while sexual reproduction is limited the long-lived Tillandsia landbeckii plant secures genotypes with high phenotypic variation via clonal propagation. As a consequence, a mosaic of such clonally reproducing vegetation units is securing not only genetic and phenotypic variation but also the integrity of the entire vegetation system thereby buffering environmental stress at the limits of vascular plant life. On longer time scales spanning hundreds to thousands of years, genetic variation is increased by rare and occasional gene flow, but the success of contemporary vegetation dynamics relies also on clonally reproduced ramets.